Meaning, Style And Emotional-Expressive Functions Of Synonyms In Artistic Text: On The Example Of Chingiz Aitmatov’s Work "A Century-Old Day" - Bazarova, Dildor Bakhronovna; Nazarova, Mukhlisa (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article analyzes the phenomenon of synonymy as an important linguistic device that ensures semantic precision, stylistic appropriateness, and emotional-expressive impact within the framework of a literary text. The research findings demonstrate that synonyms function as an active semantic mechanism in expressing the author’s artistic intention and philosophical perspectives.